2013
DOI: 10.1021/bi401178y
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinase Delta Promotes Lipogenesis

Abstract: We have studied the relationship between diacylglycerol kinase delta (DGKδ) and lipogenesis. There is a marked increase in the expression of DGKδ during the differentiation of 3T3-L1 cells to adipocytes, as well as in the synthesis of neutral and polar lipids. When 3T3-L1 undifferentiated fibroblasts are transfected to express DGKδ there is increased triglyceride synthesis without differentiation to adipocytes. Hence, expression of DGKδ promotes lipogenesis. Lipid synthesis is decreased in DGKδ knockout mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…In cultured preadipocytes, DGK␦ silencing caused a concomitant decrease of DAG, PA, and triglycerides (28). DGK overexpression in preadipocytes promotes lipogenesis (37), consistent with a role for DGK in lipid storage in fat cells. Skeletal muscle contains substantially less total lipid than adipocytes, so the pool of DAG and PA regulated by DGK␦ may comprise a major portion of total lipid available for storage and oxidation.…”
Section: Discussionmentioning
confidence: 54%
“…In cultured preadipocytes, DGK␦ silencing caused a concomitant decrease of DAG, PA, and triglycerides (28). DGK overexpression in preadipocytes promotes lipogenesis (37), consistent with a role for DGK in lipid storage in fat cells. Skeletal muscle contains substantially less total lipid than adipocytes, so the pool of DAG and PA regulated by DGK␦ may comprise a major portion of total lipid available for storage and oxidation.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, Shulga et al (37) and Lowe et al (38) reported that DGK␦ positively regulated lipid synthesis, including DG and PA, during adipocyte differentiation. However, unlike for acute high glucose stimulation, a significant preference against DG and PA was not found.…”
Section: Discussionmentioning
confidence: 99%
“…Once generated, PtdOH can mediate signaling events by indirect mechanisms through metabolism into other bioactive lipids such as LPA by phospholipase A (Aoki, 2004) and DAG by lipid phosphate phosphatase (Brindley, 2004). PtdOH constitutes between 2 and 6% in the cellular membranes and that accounts for about 10% of the PC content (typically 30-50% of the total glycerophospholipids, depending on the biologic source) of the membranes (Andreyev et al, 2010;Shulga et al, 2013). By comparison, LPA is typically found to be less than 1% (nanomolar quantities) (Sugiura et al, 1999;Jesionowska et al, 2014), whereas total PIP n represents less than 1% of the membrane phospholipids (Czech, 2000).…”
Section: Functions Of Phosphatidic Acidmentioning
confidence: 99%